Cyber Resilience Evaluation Using Cyber Resilience Review Framework at University XYZ - Ahmad Maulana Fikri; Lovinta Happy Atrinawati; Muhammad Gilvy Langgawan Putra (International Journal of Educational Management and Innovation, 2022)
Cyber resilience is about protecting data and information owned by University XYZ and adapting business processes at University XYZ to ensure service continuity when cyber threats occur. However, University XYZ never evaluates its practices to implement security and data management. University XYZ needs to know its maturity level based on cyber resilience evaluation to improve its cyber resilience. Therefore, this research was carried out to evaluate cyber resilience at University XYZ using the Cyber Resilience Review (CRR) assessment by evaluating ten cyber resilience domains. The evaluation covers academic services that use the University XYZ academic information system. The evaluation process will be held through an interview with the process owner. The interview questions are based on CRR assessment. After the evaluation, we found that none of the domains in University XYZ had yet reached Maturity Indicator Level (MIL)-1. In addition, the overall performance percentage for each CRR domain had not yet reached 100%. An improvementrecommendation for each domain has also been made, containing guidance for implementing incomplete and noncommitted practices. University XYZ can implement cyber resilience practices according to recommendations so that the implementation process can run optimally, even thoughcyber threats occur from time to time.